Clinicopathological characteristics and management of prostate cancer in the human immunodeficiency virus (HIV)‐positive population: experience in an Australian major HIV centre. (28th August 2015) - Ong, Wee Loon; Manohar, Paul; Millar, Jeremy; Royce, Peter
Abstract : Objectives: To characterise clinicopathological characteristics of prostate cancer among human immunodeficiency virus (HIV)‐positive men and to evaluate the current practice patterns in the management of prostate cancer in these men. Patients and Methods: We retrospectively reviewed all patients with HIV in the State‐wide HIV referral centre in Victoria, who were diagnosed with prostate cancer from 2000 onwards. In all, 12 patients were identified, and the medical records were reviewed to collect data on HIV parameters at the time of prostate cancer diagnosis, as well as prostate cancer clinicopathological characteristics, treatment details and outcomes. Results: At the time of prostate cancer diagnosis, eight patients had undetectable viral load, and the median cluster of differentiation 4 (CD4) count was 485 cells/μL. The average age at diagnosis of prostate cancer was 63 years and the median prostate‐specific antigen (PSA) level of 11.1 ng/mL. Four patients had Gleason 6 prostate cancer, four Gleason 7, one Gleason 8 and three Gleason 9. Seven of the 12 patients had a positive family history for prostate cancer. Of the patients with clinically localised prostate cancer (10), most were treated with radiotherapy (RT): one permanent seed brachytherapy (BT), five external beam RT (EBRT), two open radical prostatectomies (RP), one active surveillance (AS), and one on watchful waiting (WW). For the two patients with metastatic disease, one had androgen‐deprivation therapy and EBRT, while the other had a combination of EBRT and chemo‐hormonal therapy with doxetacel. All patients were followed for a median of 46 months, with three deaths reported, none of which was a prostate cancer‐specific death. Conclusions: This is the first Australasian series on prostate cancer management in a HIV population. With the prolonged survival among HIV‐positive men in the highly active anti‐retroviral therapy era, PSA testing should be offered to this group of patients, especially those with a positive family history. HIV‐positive men should also be offered all treatment options in the same manner as men in the general population.